Baumarten-Atlas zur dritten Bundeswaldinventur (BWI 2012); Tree species atlas of the third national forest inventory (BWI 2012) - Franz Kroiher; Friedrich Schmitz (Johann Heinrich von Thünen-Institut, 2015)
Die deutsche Bundeswaldinventur (BWI) ist eine systematische Stichprobeninventur, die im 4 km x 4 km-Grundnetz mit regionalen Netzverdichtungen die Waldverhältnisse in ganz Deutschland aufzeigt. Insgesamt 51 Baumarten werden in der BWI erfasst. Der vorliegende Baumartenatlas gibt an, wie standortgerecht die 31 wichtigsten Baumarten in Deutschland sind. Eine Baumart wird je nach vorhandener natürlicher Waldgesellschaft als eine Pionierbaumart, eine akzessorische oder obligatorische Klimaxbaumart bzw. als eine Baumart außerhalb des natürlichen Verbreitungsgebiets kategorisiert. Die Kategorisierung ist bedeutsam für die Ableitung des Naturnähegrads der Baumartenzusammensetzung in der BWI. – – The National Forest Inventory (BWI) records the forest conditions in Germany in a systematic sample inventory on the basis of a 4 km x 4 km reference grid with regional grid refinements. The BWI distinguishes a total of 51 tree species or tree species groups. This tree atlas informs about the distribution and the ecological relevance of the 31 most important tree species in Germany in the natural forest community of a sample point. It separately outlines the categories of pioneer tree species, accessory or mandatory climax tree species or tree species outside the natural distribution area. [...] The categorization is, for instance, the basis for determining the naturalness of the tree species composition in the BWI.
urn:nbn:de:gbv:253-201511-dn055892-4
Keywords: Q23; 630; Bundeswaldinventur; Baumartenvorkommen; natürliches Verbreitungsgebiet; heutige potenzielle natürliche Vegetation; Pionierbaumart; Klimaxbaumart; national forest inventory; tree species occurrence; natural range; potential natural vegetation; pioneer tree species; climax tree species